Capacity optimization of hybrid long-term and short-term energy storage systems for offshore wind power considering operational strategy - LIU Xiaoyu, CHENG Beibei, TANG Lang, ZHU Chengcheng, WANG Peng, TAO Hai (Ziyuan Kexue)
[Objective] The development of high-quality offshore wind power is not only an important part of China's efforts to establish a new-type power system, but also a critical safeguard for building a strong maritime nation. Exploring feasible solutions to alleviate the supply-demand mismatch in offshore wind power can enhance its consumption capacity while achieving substantial economic benefits, thereby providing strategic insights for high-quality development of offshore wind power during capacity optimization stage. [Methods] This study integrated the strategies of reducing discharge frequency of short-term energy storage and participating in peak shaving for long-term energy storage. Under the target constraint of wind curtailment rate (RCUR) not exceeding 5%, with the objectives of optimizing loss of load probability (LOLP) and net present value ratio(NPVR), technology-energy-economy optimization evaluation model was established to optimize the configuration of short-term and long-term energy storage. A year-long simulation of energy storage charging and discharging was conducted. The impacts of two short-term storage technologies, the lithium-ion battery（LI）with high charge-discharge efficiency and the flow battery (FB) with high charge-discharge cycle life, and one long-term energy storage technology, pumped hydro storage, on system energy utilization, energy supply reliability, and economic benefits were also evaluated. [Results] The proposed optimization method yielded more economically efficient configuration schemes. The net present value (NPV) increased by a maximum of 1.897 billion yuan, with annual additional peak shaving electricity sales revenue from long-term energy storage reaching 98 million yuan. Moreover, it effectively extended the service life of short-term energy storage by 1 to 2.6 times. The optimized configuration enhanced the utilization of wind curtailment by approximately 64%. Comparative analysis revealed that the limitations of charge-discharge cycles had a greater influence on the economic efficiency of short-term energy storage system than charge-discharge efficiency. [Conclusion] Energy storage capacity design requires integrated planning. Application methods and operational policies for energy storage should fully consider system performance and the application potential for residual storage capacity. The correlation between the high-quality development of offshore wind power and the enhanced performance of long-term energy storage systems should not be overlooked.